Multimodal texts : strengthening productive competences while addressing gender stereotypes in the EFL classroom. (2021)
Stereotypes are ingrained in our society causing a big impact on people’s self-image and perception about others, especially those stereotypes that deal with gender. Accordingly, schools should address those topics in their classrooms to create inclusive environments where students can listen to each other and communicate their ideas about such subjects. Consequently, the current paper presents a pedagogical and didactic proposal based on the use of multimodal texts with social content to address gender stereotypes and to strengthen productive competences in the EFL classroom, all within a framework of critical literacy. The proposal has been planned for tenth graders of public schools in Bogotá, Colombia, whose ages range between fifteen and seventeen years old. Furthermore, due to the recent situation with the COVID-19 pandemic, the activities within this project are designed to be conducted in both remote and in-person environments. The pedagogical design has been organized in three cycles containing a total of five lesson plans to be developed with eleven sessions of one hour and a half. Each session presents a variety of multimodal texts addressed within the critical literacy approach that will promote students' productive competences.